Representations and use intention of phytoterapy in primary health care - da Rosa, Caroline; Sheila Gonçalves Câmara; Béria, Jorge Umberto (Ciência & saude coletiva, 2011)
The current observational study of investigative characteristics aimed to identify the representations and the use of phytotherapy on the primary health care and the factors related to the intention of use of this therapy. The population for this study was composed by 27 physicians from the Family Health Program in the city of Canoas, Rio Grande do Sul State, Brazil. This quality approach research was developed through a semi structured interviewing process embracing: conceptualization, experiences with phytotherapics and phytotherapy on primary health care. Such topics have brought up subcategories like attitudes, peers perception, control over prescription and intention of use of phytotherapics on primary care. The results have shown that the physicians do not have an institutional knowledge about the subject; a greater intention of use is related to the knowledge of the professionals on this therapeutic modality, based on the belief of its scientific evidence. In order to institutionalize phytotherapy in primary health care a more spread promotion of the studies on scientific evidences is necessary, as well as investments in improvements of professional skills. Thus, the general population will be able to benefit from phytotherapy as a more accessible alternative to health care